Bringing Stalin Back In : memory politics and the creation of a useable past in Putin's Russia - Nelson, Todd H. (Lanham: Lexington Books, 2019)
"This book examines the favorable portrayal of Stalin in Russia today. Putin and the political elite have co-opted the processes of discourse formulation in Russian society, using these to advance positive perceptions of Stalin, while exercising control over the arenas in which any sort of alternative narratives on Stalinism might emerge"--
Includes bibliographical references (pages 143-154) and index.
Keywords: Stalin, Joseph, -- 1878-1953 -- Public opinion; Putin, Vladimir Vladimirovich, -- 1952- -- Influence; Public opinion -- Russia (Federation); Collective memory; Political culture